THANKS SVETLANA: PRIVACY, TRUST, HUMOR, AND THE RUSSIAN PSYOP ON TUMBLR - Neill Hoch, Indira (AoIR Selected Papers of Internet Research, 2019)
This study uses a combination of multimodal discourse analysis (Bateman, 2008; Holsanova, 2012; Jewitt, 2009; LeVine & Scollon, 2004) and qualitative interview materials to make an initial attempt at understanding the response to the Russian Psyop as it played out on Tumblr. It is critical that we, as technologically-oriented, civically concerned communication scholars, understand the technical and social mechanisms that allowed Russian and other interference on social media platforms to be perpetuated, and not only on the most popular and visible sites, such as Facebook and Twitter, but more niche platforms as well. Interview materials originate prior to the announcement, and were conducted from September to November 2017. In these interviews, privacy concerns were discussed at length, as well as Tumblr’s perceived incompetence when coding and maintaining a web platform. Because they maintained relatively little faith in the digital architecture of Tumblr, participants instead largely managed their privacy by carefully considering who they followed and who followed them. This centrality of “knowing” who they followed (while almost never knowing the blogger in a face-to-face context) is key for understanding how the Russian accounts must resemble “real” people, in order to gain followers and thus traction on Tumblr. The posts and reblog chains under analysis either 1) originated with one IRA-linked account, “lagonegirl,” and were reblogged after “her” blog was deleted, or 2) were humorous responses to the Psyop revelation/Russian spies.